Odpowiedź :
a²+2ab+c²
25-20e+4e²
36+6d-6d-d²=-d²+36
5a+1
8f-10
2a-8-3a²+15a=-3a²+17a-8
25-20e+4e²
36+6d-6d-d²=-d²+36
5a+1
8f-10
2a-8-3a²+15a=-3a²+17a-8
(a+b)²=(a+b)*(a+b)=a²ab+ba*b²
(5-2e)²=(5-2e)*(5-2e)=25*52e-2e5*2e²
a dalej nie umiem a nie wiem czy mam tanto dobrze...
(5-2e)²=(5-2e)*(5-2e)=25*52e-2e5*2e²
a dalej nie umiem a nie wiem czy mam tanto dobrze...
(a+b)²=a²+2ab+b²
(5-2e)²=25-20e+4e²
(6-d)(6+d)=6²-d²=36-d²
(3+4a)-(2-a)=...
2(3f-5)+2f=6f-10+2f=8f-10
-2(-a+4)-3a(a-5)=2a-8-3a²+15a=-3a²+17a-8
(5-2e)²=25-20e+4e²
(6-d)(6+d)=6²-d²=36-d²
(3+4a)-(2-a)=...
2(3f-5)+2f=6f-10+2f=8f-10
-2(-a+4)-3a(a-5)=2a-8-3a²+15a=-3a²+17a-8